Improving Water Management in Rainfed Agriculture : Issues and Options in Water-Constrained Production Systems - World Bank (Washington, DC, 2013)
Due to climate change and increasing food prices, emphasis needs to be placed on addressing water management as a key determinant for agricultural production and productivity. However, governments and donors have tended to pay relatively little attention to this area, and investments remain low. This report, which is based on economic and sector work carried out in the Water Anchor of the World Bank, highlights the importance of improving water management in rainfed agriculture, with a focus on those production systems where water is a main constraint. It provides a synthesis of the state-of-the-art thinking and experience. Considering the various issues that are currently preventing further upscaling of these measures, and better evaluation of the feasibility of applying particular measures or combination of measures, the report proposes options and recommendations for interventions to help overcome these issues. In doing so, the report aims to stimulate discussion and encourage new thinking among World Bank staff and counterparts in client countries who work on enhancing agricultural productivity and livelihoods in rainfed agriculture through improved water management and related interventions.